The ‘Qur’an Crisis’ in the Swedish Press - Mia Lövheim (Temenos)
During the summer of 2023 news and debates about public burnings of the Qur’an dominated the Swedish and international media. In the aftermath of the flames and the debate this article aims to present and discuss the representation of the event as a ‘crisis’ in the Swedish daily press between 1 April and 1 October 2023. The article uses a quantitative analysis of the main topics in a selection of Swedish and Nordic daily newspapers, and a combination of co-occurrence and qualitative frame analysis of how the event came to be debated in a sample of Swedish opinion articles. Theories of mediatized conflicts as dynamic and complex processes revealing the state of democracy in a society are used to analyse the findings. The results are discussed in light of previous research on Qur’an burnings in Sweden and on debates about previous events involving clashes between freedom of speech and freedom of religion in the Nordic countries. The article concludes by arguing that the ‘Qur’an crisis’ as a mediatized conflict co-structures an ongoing negotiation between different positions on the most fundamental values of democracy, which has become increasingly contentious in Swedish public and political debate.